2010
DOI: 10.1038/jhg.2010.79
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to 20p13 including the ANGPT4 gene in families with mixed Alzheimer's disease and vascular dementia

Abstract: This study aimed at identifying novel susceptibility genes for a mixed phenotype of Alzheimer's disease and vascular dementia. Results from a genome scan showed strongest linkage to 20p13 in 18 families, and subsequent fine mapping was performed with both microsatellites and single-nucleotide polymorphisms in 18 selected candidate transcripts in an extended sample set of 30 families. The multipoint linkage peak was located at marker rs2144151 in the ANGPT4 gene, which is a strong candidate gene for vascular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…ANGPT4 (angiopoietin 4) encodes a protein involved in angiogenesis and has been associated with cases of mixed AD/vascular dementia in family-based studies [45]. Meta-analysis results summarizing prior studies has indicated that past diagnosis of depression confers heightened risk for AD later in life [46].…”
Section: Discussionmentioning
confidence: 99%
“…ANGPT4 (angiopoietin 4) encodes a protein involved in angiogenesis and has been associated with cases of mixed AD/vascular dementia in family-based studies [45]. Meta-analysis results summarizing prior studies has indicated that past diagnosis of depression confers heightened risk for AD later in life [46].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of genetic loci that modify vessel growth has been an area of increasing interest in clinical and preclinical research. [22][23][24][25][26][27] Whereas the genes behind these loci are potentially powerful tools for risk assessment and therapeutic intervention, angiogenesis is intimately associated with tissue development and survival, limiting our ability to identify genetic factors regulating vessel growth by use of genetargeting approaches. 28 However, the use of model systems by us and others 19,20 in various tissue-specific assays, by use of vessel growth as a complex trait, is beginning to find novel genes that also control vessel growth.…”
Section: Discussionmentioning
confidence: 99%
“…However, THBS1 and SERPINE1 have been identified as anti-angiogenic [11] [13] . Angiopoietin ANGPT4 is a protein that promotes angiogenesis [14] . Fractalkine (FKN)-induced activation of CX3CR1 in EC leads to in vivo angiogenesis through the induction of HIF-1alpha and VEGF-A gene expression by CX3CR1 activation and subsequent VEGF-A/KDR-induced angiogenesis [15] .…”
Section: Methodsmentioning
confidence: 99%